ILAE type 3 hippocampal sclerosis in patients with anti-GAD–related epilepsy. Issue 4 (August 2015) - Glover, Robert L.; DeNiro, Lauren V.; Lasala, Patrick A.; Weidenheim, Karen M.; Graber, Jerome J.; Boro, Alexis
Abstract : Objective: To describe the neuropathologic findings and clinical course of 2 patients who underwent temporal lobectomy for medically refractive epilepsy and were later found to have high anti–glutamic acid decarboxylase (GAD) concentrations. Methods: Small case series. Results: Neuropathologic examination of both patients revealed International League Against Epilepsy (ILAE) type 3 hippocampal sclerosis. Following surgery, both developed signs and symptoms of stiff person syndrome and later cerebellar ataxia. Laboratory studies demonstrated high concentrations of anti-GAD antibodies in both patients. Conclusions: These cases suggest that ILAE type 3 hippocampal sclerosis may be immunologically related to and may exist as part of a broader anti-GAD–related neurologic syndrome in some instances.